Some general classes of comatching graphs - E. J. Farrell; S. A. Wahid (International Journal of Mathematics and Mathematical Sciences)
Some sufficient conditions are given for two graphs to have the same matching polynomial (comatching graphs). Several general classes of comatching graphs are given. Also, techniques are discussed for extending certain pairs of comatching graphs to larger pairs of comatching graphs.